Early Detection of Cardiovascular Risk in Pediatric Populations: Are We Doing Enough Compared to Adult Protocols? Early Detection of Cardiovascular Risk in Pediatric Populations - Munir, Ussama; Naeem, Muhammad; Shafiq, Umar; Ahmad, Iftikhar; Rehman, Fazal Ur; Zafar, Muhammad Adnan; Haq, Anwar Ul (Pakistan Journal of Health Sciences, 2025)
Cardiovascular diseases, once considered primarily adult health concerns, are increasingly being traced back to risk factors emerging during childhood. Objectives: To evaluate the early detection of cardiovascular risk factors in pediatric populations and compare current pediatric screening practices with established adult protocols in a low-resource setting. Methods: This was a cross-sectional analytical study conducted at the Department of Pediatric Cardiology, Quaid-e-Azam Medical College, Bahawalpur, from March 2024 to March 2025. A total of 341 children aged 5–12 years were enrolled using non-probability consecutive sampling. Data were collected through structured interviews, anthropometric measurements, blood pressure readings, and fasting laboratory investigations, including lipid profile, fasting blood glucose, HbA1c, and serum. Participants were stratified by BMI, lifestyle, and family history. Results: Obesity was observed in 8.2% of participants, and 27.3% had a waist-to-height ratio ≥0.5. Hypertension was identified in 27.0% of children and dyslipidemia in 38.7%. Low HDL (<45 mg/dL) was seen in 46.6%, and triglycerides ≥130 mg/dL in 38.7%. Vitamin D deficiency (<20 ng/mL) was found in 66.6%, with a significant inverse correlation with triglyceride levels (r=–0.41, p<0.001). Obesity (OR 3.67, 95% CI: 2.10–6.41, p< 0.001), sedentary lifestyle (OR 2.34, 95% CI: 1.33–4.12, p=0.004), and family history of CVD (OR 2.26, 95% CI: 1.30–3.95, p=0.003) were significant predictors. Conclusions: The high prevalence of early cardiovascular risk factors in Pakistani children highlights the urgent need for structured pediatric screening protocols.